Molecular dynamics simulations and conductance studies of the interaction of VP1 N-terminus from Polio virus and gp41 fusion peptide from HIV-1 with lipid membranes - Hong, Guo-Sheng; Fink, Rainer (Molecular membrane biology, 2012)
The icosahedral Polio virus capsid consists of 60 copies of each of the coat proteins VP1, VP2, VP3 and myristolyated VP4 (myrVP4). Catalyzed by the host cell receptor the Polio virus enters the host cell via externalization of myrVP4 and the N terminal part of VP1. There are several assumptions about the individual role of both of the proteins in the mechanism of membrane attachment and genome injection. We use the first 32 N terminal amino acids of VP1 and applied molecular dynamics simulations to assess its mechanism of function when attached and inserted into hydrated lipid membranes (POPC). Helical models are placed in various positions in regard to the lipid membrane to start with. As a comparison, the first 33 amino acids of the fusion peptide of gp41 of HIV-1 are simulated under identical conditions. Computational data support the idea that VP1 is not penetrating into the membrane to form a pore; it rather lays on the membrane surface and only perturbs the membrane. Furthermore, this idea is strengthened by channel recordings of both peptides showing irregular openings.
Gesehen am 29.08.2018